The role of professional ethics components on job knowledge sharing and organizationalflourishing of employees of the General Department of Sports and Youth in Isfahan province: * Corresponding Author:Masoome Hosseini، Assistant Professor, Department of Sports Management, Payam Noor University, Tehran, Iran Iran, Email: mhosseini_phd@yahoo.com ORCID:0000-0002-6329-948X - Hosseini, Masoome; Rajaei Azarkhavarani, Marzieh; Kordmirza Nikoozadeh, Ezzatollah (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim: The present research was designed and implemented with the aim of the role of professional ethics components on the sharing of professional knowledge and organizational flourishing of employees of the General Directorate of Sports and Youth in Isfahan province. Materials and Methods:This research is descriptive and correlational in terms of applied purpose. The data was collected in the field and through a questionnaire. The statistical population of all employees of the General Directorate of Sports and Youth of Isfahan province is 296 people. Due to the limitedness of the statistical population, a sample similar to the population was considered. Data analysis was done using SPSS and AMOS software. Findings: The results of the research showed that the path coefficient of the relationship between attachment and interest in work on job knowledge sharing is 0.392 and on flourishing is 0.187. The results of persistence and seriousness on job knowledge sharing is 0.123 and on flourishing is 0.222. Healthy relationships on job knowledge sharing is 0.240 and on flourishing is 0.466. Collective spirit and participation in work is 0.256 on job knowledge sharing and 0.320 on growth. Conclusion: The study shows that there is a positive and meaningful relationship between the components of professional ethics, job knowledge sharing and organizational flourishing of employees of the General Directorate of Sports and Youth in Isfahan province